Common‐Volume Dual‐Frequency Radar Observations of 150‐km Echoes and Implications. Issue 1 (8th January 2020) - Patra, A.K.; Chaitanya, P. Pavan; Rao, M. Durga; Kamaraj, P.
Abstract: We present and discuss common‐volume dual‐frequency radar observations of 150‐km echoes made at 30 and 53 MHz from Gadanki by employing identical transmitter power and antenna beam width. These controlled experiments reveal that 150‐km echoes are stronger, broader in spectral width, and more frequent in their occurrence at 30 MHz than at 53 MHz. Echo intensities at 30 and 53 MHz are found to be consistent with the rocket‐borne observations of wave number spectrum of meter‐scale irregularities in the 150‐km region. The frequency dependence of spectral widths of the echoes while is found to be somewhat similar to that of electrojet type‐1 echoes it is opposite to that of electrojet type‐2 echoes and also to that of incoherent scattering in direction perpendicular to magnetic field. Spectral widths of the echoes observed by both radars are found to be independent of SNR. A detailed comparison of these observations with those made earlier suggests that instrument functions play an important role in manifesting SNR‐dependent/independent spectral width property of the 150‐km echoes. The narrow spectral properties and frequency dependence of echo intensity and spectral width clearly suggest that the irregularities responsible for the radar backscatter are linked with weak plasma turbulence and the meter‐scale irregularities responsible for radar echoes ought to be growing with direct injection of energy at the meter scale itself to overcome damping. We surmise the potential role of photoelectrons and atmospheric gravity waves in the underline plasma instability process. Key Points: Dual‐frequency radar observations reveal that 150‐km echoes are stronger and broader in spectral width at 30 MHz than at 53 MHz Frequency dependence of echo intensity is consistent with in situ observed wave number spectrum Results suggest the role of plasma instability enabling direct excitation of meter‐scale irregularities responsible for the radar echoes